220k views
2 votes
3x/x^ 2 - 6x = 1 . Solve for x.

2 Answers

3 votes

Answer:

X=-3

Explanation:

User Argote
by
5.0k points
3 votes

Answer:

Explanation:

3x/x^ 2 - 6x = 1

3/x - 6x = 1

Multiply each term by x

3 - 6x² = x

6x² + x - 3 = 0

Using quadratic formula

X = [-b ± √(b² - 4ac)]/2a

a = 6, b = 1 and c = -3

X = [-1 ± √(1² - 4(6×-3)]/(2×6)

X = [-1 ± √(1 +72)]/12

X = [-1 ± √73]/12

X = [-1 ± 8.54]/12

X = (-1 + 8.54)/12 or (-1 - 8.54)/12

X = 7.54/12 or -9.54/12

X = 0.63 or - 0.8

User Nuno
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.